Premarital hepatitis screening: Attitude towards screening and the risk factors for transmission - Alharbi, Ibtehaj M. (Saudi Med J, 2018)
OBJECTIVE: To explore all research articles investigating hepatitis premarital screening programs (PSPs) worldwide, considering all different outcomes of such programs, including efficacy, possible limitations to screening, and participants’ knowledge and satisfaction regarding the program. METHODS: The present systematic review used the databases of PubMed, Ovid Medline, and Google Scholar to search for articles related to both PSPs and the hepatitis viruses. Research articles were identified between October and December 2017, and articles were selected and extracted based on predefined inclusion and exclusion criteria from the year 1957 up to 2017. The review included all full-length original articles related to premarital hepatitis screening in both indexed and non-indexed journals, but reviews, mini-reviews, and letters were excluded. Ultimately, 4 research papers were included. While conducting the search, the project was registered on PROSPERO database. RESULTS: In all these papers, the participants’ attitude toward premarital screening was good, but their level of knowledge about the program and the diseases being screened was low. Pre- and post-test counseling were provided to only a limited number of participants in each of the studies. This emphasizes the need for effective counseling sessions, which may help in decreasing the hepatitis burden in Saudi Arabia and worldwide. CONCLUSIONS: The role of the practicing physician in any screening program is to provide effective pre and post-test counseling and correct any misinformation about the transmission of the hepatitis viruses. PROSPERO Registration number: CRD42018096535